2006
DOI: 10.4319/lom.2006.4.58
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AUV-based ADCP measurements

Abstract: Recent development and commercialization of relatively portable and inexpensive autonomous underwater vehicles (AUVs) have led to new methods for making hydrodynamic, chemical, and biological measurements in near-coastal, lake, and estuarine systems. Equipped with Doppler velocity log (DVL) technology to allow for deadreckoning navigation, this new class of AUVs has the potential to log not only vehicle motions, but water velocities as well. In this article, we assess the performance of the DVL acoustic Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Our earlier work has shown that the REMUS ADCP can be effective in resolving steady BL structure with spatial averaging of 50-100m (Jaramillo & Pawlak, 2010a). Analysis of along-track velocities has shown evidence of weak velocity bias in the direction of platform motion in agreement with other observations from vessel and AUV-mounted ADCPs (Fong & Monismith, 2004;Fong & Jones, 2006). In Jaramillo & Pawlak (2010a), we further characterize the variability in this bias with sampling.…”
Section: Approachsupporting
confidence: 86%
“…Our earlier work has shown that the REMUS ADCP can be effective in resolving steady BL structure with spatial averaging of 50-100m (Jaramillo & Pawlak, 2010a). Analysis of along-track velocities has shown evidence of weak velocity bias in the direction of platform motion in agreement with other observations from vessel and AUV-mounted ADCPs (Fong & Monismith, 2004;Fong & Jones, 2006). In Jaramillo & Pawlak (2010a), we further characterize the variability in this bias with sampling.…”
Section: Approachsupporting
confidence: 86%
“…Results of missions performed in 2011 by OSU off the Oregon Shelf and in the Sargasso Sea are available in [8]. It is important to note that errors or missing data may occur in current measurement from on-board ADCP/DVL [9]. The ADCP manufacturer claims to have an accuracy of 1 % of the measured current magnitude ± 5mm/s.…”
Section: Introductionmentioning
confidence: 98%
“…Acoustic Doppler Current Profilers (ADCPs) were originally implemented by scientists on aquatic AVs to provide dead-reckoning navigation based on a Doppler Velocity Log (DVL) [7]. However, ADCPs have recently been used on AVs to measure features including coastal ocean flows [1,5,7,13,18], directional surface waves [12], and depthaveraged currents [6]. There is an increasing need for collecting environmental data with AVs in faster and more dynamic flows found in riverine and estuarine environments.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure a true estimate of the mean velocity is obtained when evaluating an appropriate averaging window, and to eliminate errors due to spatial variability from moving-vessel measurements, only measurements obtained by the vessels at fixed locations are considered in this work. Acoustic Doppler Current Profilers (ADCPs) were originally implemented by scientists on aquatic AVs to provide dead-reckoning navigation based on a Doppler Velocity Log (DVL) [7]. However, ADCPs have recently been used on AVs to measure features including coastal ocean flows [1,5,7,13,18], directional surface waves [12], and depthaveraged currents [6].…”
Section: Introductionmentioning
confidence: 99%